The case report of MOG and NMDAR IgG double positive encephalitis treated with subcutaneous ofatumumab - Zhang, Rui; Wang, Li; Tao, Yongli; Zhang, Xiaofeng; Liu, Kai; Song, Bo; Xu, Yuming (Frontiers in Immunology, 2023)
The phenotypic spectrum of myelin oligodendrocyte glycoprotein (MOG)- IgG–associated disorders (MOGAD) has broadened in the past few years, and atypical phenotypes are increasingly recognized. Isolated seizures and MRI-negative brainstem and cerebellar symptoms or encephalitis have rarely been reported as a feature of MOGAD and represent a diagnostic challenge. Meanwhile, the coexistence of MOG IgG and other CNS autoimmune antibodies is infrequent. We report a patient presented with isolated epileptic onset, relapsed with MRI-negative brainstem symptoms and MRI-negative encephalitis. He was positive for MOG IgG throughout the disease course while concomitant NMDAR IgG was not detected positive until second relapse. He showed decreasing response to conventional first-line therapy. The last relapse was during a COVID-19 epidemic with limited inpatient resources. Fortunately, he was ultimately controlled on subcutaneous ofatumumab, a novel fully humanized anti-CD20 mAb. This is the first report about subcutaneous ofatumumab treatment in MOG and NMDAR IgG double positive encephalitis with 12-month follow-up, depicting its potential as a therapeutic option.